Resource Center System (RECENTSYS) - Sulaiman, Khairul Asyrani; Samin, Mohd Hizam (Universiti Teknologi MARA, Kedah, 2017)
ReCentSYS is an all-in-one system and easy-to-use library management system which is ideal for small and midsize libraries ranging from school to public institutions and companies. It consists of web-based front/back-end portal and a mobile app for accessing the library catalogue on the go. The portal is very user friendly for library starters. It has been developed from the ground up by Tuanku Bainun Library, UPSI using open source technology and compliance to the MARC 21 standard. Library system is often very hard to use and maintained by non library personnels. Challenged by the current situation, Tuanku Bainun Library with dedicated librarians and IT personnel strive to develop a new all-in-one system for small-to-mid size library to begin their journey for providing their user with easy to use system to access the library materials.